1984
DOI: 10.3109/00016488409132919
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration Cytology in Acute Otitis Media

Abstract: One hundred and ninety-three middle ear effusion samples from patients with acute otitis media were studied for cellular content and bacteria. Findings were compared with clinical and radiological data. In samples positive for pathogenic bacteria (Haemophilus, pneumococci) neutrophils predominated, whereas monocytes or phagocytes were more numerous in samples with nonpathogens. Inflammatory cells were more frequent in large than in small mastoid air cell systems. Destruction of cell walls was associated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 4 publications
1
5
0
2
Order By: Relevance
“…S100A12 serum level increases during an AOM episode are likely related to neutrophil activation in response to an increase in bacterial load in the nasopharynx during a viral URI that sets the stage for pathogenesis resulting in AOM. This observation is consistent with differences in pathogen-stimulated activation of neutrophils previously observed by others [21,22]. Also, the number of neutrophils in Middle Ear Fluid (MEF) of children with AOM caused by Spn has been shown to be significantly higher than that found in the MEF of children with AOM caused by NTHi [23].…”
Section: Discussionsupporting
confidence: 91%
“…S100A12 serum level increases during an AOM episode are likely related to neutrophil activation in response to an increase in bacterial load in the nasopharynx during a viral URI that sets the stage for pathogenesis resulting in AOM. This observation is consistent with differences in pathogen-stimulated activation of neutrophils previously observed by others [21,22]. Also, the number of neutrophils in Middle Ear Fluid (MEF) of children with AOM caused by Spn has been shown to be significantly higher than that found in the MEF of children with AOM caused by NTHi [23].…”
Section: Discussionsupporting
confidence: 91%
“…Qvarnberg et al (13) also found a higher number of neutrophils in AOM caused by Spn than in AOM cases in which no pathogens were isolated. The significant increase of S100A12 serum concentrations in children with AOM may be related to the activation, proliferation and recruitment of neutrophils and other inflammatory cells to the middle ear site.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, obviously a simple comparison of bacterial-positive rates cannot definitively conclude a correlation of direct bacterial dissemination into the middle ear cavity by adenoid hypertrophy and sinusitis and OME. Qvarnberg et al (11) stated that the bacteria-positive rate was higher in middle ear effusions with purulent fluid, however, there was no significant difference between those with mucoid and serous fluid. In this study, we presume that since the serous fluid specimens were much fewer than the mucoid fluid specimens, there were no statistically significant results and further study will be necessary.…”
Section: Discussionmentioning
confidence: 99%